Impact of Treatment Beyond Progression with Immune Checkpoint Blockade in Hodgkin Lymphoma. (28th April 2020) - Merryman, Reid W.; Carreau, Nicole A.; Advani, Ranjana H.; Spinner, Michael A.; Herrera, Alex F.; Chen, Robert; Tomassetti, Sarah; Ramchandren, Radhakrishnan; Hamid, Muhammad; Assouline, Sarit; Santiago, Raoul; Wagner‐Johnston, Nina; et al.
Abstract: Atypical response patterns following immune checkpoint blockade (ICB) in Hodgkin lymphoma (HL) led to the concept of continuation of treatment beyond progression (TBP); however, the longitudinal benefit of this approach is unclear. We therefore performed a retrospective analysis of 64 patients treated with ICB; 20 who received TBP (TBP cohort) and 44 who stopped ICB at initial progression (non‐TBP cohort). The TBP cohort received ICB for a median of 4.7 months after initial progression and delayed subsequent treatment by a median of 6.6 months. Despite receiving more prior lines of therapy, the TBP cohort achieved longer progression‐free survival with post‐ICB treatment (median, 17.5 months vs. 6.1 months, p  = .035) and longer time‐to‐subsequent treatment failure, defined as time from initial ICB progression to failure of subsequent treatment (median, 34.6 months vs. 9.9 months, p  = .003). With the limitations of a retrospective study, these results support the clinical benefit of TBP with ICB for selected patients. Abstract : To investigate the potential benefit of treatment beyond progression in patients with Hodgkin lymphoma, a multicenter retrospective analysis of 64 patients treated with immune checkpoint blockade was performed. Some patients stopped therapy at initial progression and some received treatment beyond progression. Results are reported here.